LOST IN TRANSLATION. - Lefkowitz, Larry (Krytyka Literacka, 2017)
The author talks about an factual error by a publisher of his works, in which the publisher had wrongly claimed that an English short story was translated from Polish, when it was actually translated from Hebrew language. He tells about his panic and how he requested an acquaintance of his to represent to accept an award from a Polish literary association for the Polish translation of the same work.